Penatalaksanaan Fisioterapi Pada Penderita Asma Eksaserbasi Akut Di Balai Besar Kesehatan Paru-Paru Masyarakat (BBKPM) Surakarta - Atmaja, Bhembie Wira; , Isnaini Herawati, S.Fis, S.Pd, M.Sc (2015)
Background: Asthma is inflamatory disease of respiratory tract that has a low fatality rate, but there was found high incidency rate in the society. Asthma can happened in all of people from children until adults. First, asthma is genetic deisease which is declined by their parents to their children. Air pollution and bad clean area is one of factors which increase asthma attack. Purpose: To know is nebulizer and diaphragmatic breathing can reduce the dypsneu in asthma patient at Great Hall Lungs Health Surakarta Society. Method: Methods in handling this case with nebulizer and diaphragmatic breathing, using evaluated borg scale. Result: After 6th therapy, the result is dypsneu reduction,before therapy 7, after therapy 0. Conclution: Nebulizer and diaphragmatic breathing can reduce the dypsneu in asthma patient at Great Hall Lungs Health Surakarta Society.